Essential residues in IMC recruitment of PfGAP45 in the malaria parasite - Wong, Tatianna Wai Ying (My University, 2015)
The Plasmodium falciparum merozoite utilizes an actin-myosin motor to invade into erythrocytes, which is a part of the protein complex termed the glideosome. The glideosome provides the parasite with substrate dependent gliding motility, and is connected to the unique organelle named the inner membrane complex (IMC). The glideosome associated protein 45 (GAP45) is a crucial member of the glideosome. Here, we investigate the differential role of two post-translational modifications, specifically palmitoylation and phosphorylation, for recruitment of the protein to the IMC as well as glideosome association. Through comprehensive mutational analysis, it was shown that in addition to the N-terminal dual acylation motif, the C-terminal residues C189 and C192 must be present to mediate GAP45 recruitment to the IMC. Despite the abundant in vivo phosphorylation sites in GAP45, a phosphorylation null mutant does not affect the protein’s IMC localization. Therefore this modification may be involved in glideosome complex formation, which will be further investigated through co-immunoprecipitation and gaining structural insight of GAP45.